Association between dietary inflammatory index and gallstones in US adults - Luo, Yanling; Gao, Xiaolian; Xiao, Mingzhong; Yang, Fen; Zhu, Xinhong; Qiao, Guiyuan; Xiang, Cong; Tao, Junxiu (Frontiers in Nutrition, 2024)
Introduction Previous studies have found that diet’s inflammatory potential is related to various diseases. However, little is known about its relationship with gallstones. The present study aims to investigate the relationship between dietary inflammatory index (DII) and gallstones. Methods Data were obtained from the 2003–2020 National Health and Nutrition Examination Survey (NHANES). We used the nearest neighbor propensity score matching (PSM) with a ratio of 1:1 to reduce selection bias. Logistic regression models estimated the association between DII and gallstones. The non-linear relationship was explored with restricted cubic splines (RCS). BMI subgroup stratification was performed to explore further the connection between DII and gallstones in different populations. Results 10,779 participants were included. Before and after PSM, gallstone group individuals had higher DII scores than non-gallstone group individuals (p < 0.05). Matched logistic regression analysis showed that DII scores were positively correlated with gallstone risk (adjusted OR = 1.14, 95% CI 1.01, 1.29). The stratified analysis showed that this association was stronger in overweight or obese people (adjusted OR = 1.18, 95% CI 1.03, 1.34). RCS analysis suggested that DII and gallstones showed a “J”-shaped non-linear dose–response relationship (p non-linear <0.001). Conclusion Higher DII score is positively associated with the risk of gallstones, particularly in overweight or obese population, and this relationship is a “J”-shaped non-linear relationship. These results further support that avoiding or reducing a pro-inflammatory diet can be an intervention strategy for gallstone management, particularly in the overweight or obese population.